Pengaruh Feeding Rate yang Berbeda Terhadap Pertumbuhan dan Tingkat Kelulushidupan Benih Ikan Nila (Oreochromis Niloticus) yang Dipelihara dengan Sistem Biofloc - Zahra, Sakinah Az; Supono, Supono; Putri, Berta (Universitas Sriwijaya, 2019)
This study was aimed to analyzed growth and survival rate of tilapia with different feeding rate. Experimental design was used completely randomized design (CRD) with three treatments and three replications. The treatments tested were (A) 7% FR, (B) 5% FR, (C) 3% FR. The study was conducted using tilapia juvenile 5 cm with average weight 2 gram which was cultivated in 3,140 m3 fiber pond. The observed parameters include absolute growth, growth rate, survival rate, feed conversion rate, and water quality. The allocation of different FR of biofloc system significantly different on growth and FCR of tilapia, but was not significantly different on survival rate of fish. Treatment with 7% FR was giving the best results with absolute growth was 8,83 gram, day growth rate was 0,221 gram/day, survival rate with percentage of 89,67%, and FCR was 1,5. The optimal absolute body weight of this biofloc system was in 7,3% FR. Keywords : Biofloc, tilapia, feeding rate, the growth and the survival rate